KAJIAN AKHLAK MENURUT AL-GHAZALI, HASAN AL-BASRI, AL-MUHASIBI DAN AL-QUSYAIRI - Sinta, Dewi; Ningtias, Annisa; Nurhuda, Abid; Maulida, Fadhila Rizqi; Putri, Anggi Ariska (MAHABBAH : Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2026)
The development of morals in the field of Sufism is a central element in the Islamic historical tradition, this is evidenced by the many figures who think about the topic of morals in depth including Al-Ghazali, Hasan Al-Basri, Al-Muhasibi, and Al-Qusyairi. And the purpose of this study is to describe the opinions of each of these figures in discussing morals. The method used is qualitative with a literature study approach model and then analyzed descriptively. The results showed that the study of morals according to each figure is not only a theoretical thing, but also a foundation for transformation and forming a good personal and spiritual. Although there are slight differences in approach, the roots of good moral values and their harmony where Al-Ghazali emphasizes the role of Sufism in the formation of good morals, while Hasan Al-Basri highlights more introspection and obedience to God. Al-Muhasibi focuses on vigilance and fear of sin, while Al-Qusyairi combines morals with the principles of the correct Shari'ah, but over time, the understanding of morals in Islam continues to develop and is able to adapt to the demands of the times.